(untitled) (BIBECHANA, 2016)
Alkaloids are a group of naturally occurring chemical compounds and show immense potential of medicinal uses in traditional systems. In this work, a computational study on an alkaloid aristolochc acidid II (AA II) is presented using density functional theory, B3LYP functional employing 6-311G (d,p) basis set. Natural bond orbital analysis has been carried out to investigate the various conjugative and hyperconjugative interactions within the molecule and their second-order stabilisation energy (E(2)). The local nucleophilic reactivity descriptors such as Fukui functions (f+k, f-k), local softness (s+k, s-k) and electrophilicity indices (ω+k,ω-k) analyses have been carried out to determine the reactive sites within the molecule. The non-linear optical properties have been calculated using the same basis set. The calculated value of the first order hyperpolarisability (β0), suggests that the investigated molecule is an attractive object in future for non-linear optical properties.